Nicotiana benthamiana Kunitz peptidase inhibitor-like protein involved in chloroplast-to-nucleus regulatory pathway in plant-virus interaction - Ershova, Natalia; Sheshukova, Ekaterina; Kamarova, Kamila; Arifulin, Evgenii; Tashlitsky, Vadim; Serebryakova, Marina; Komarova, Tatiana (Frontiers in Plant Science, 2022)
Plant viruses use a variety of strategies to infect their host. During infection, viruses cause symptoms of varying severity, which are often associated with altered leaf pigmentation due to structural and functional damage to chloroplasts that are affected by viral proteins. Here we demonstrate that Nicotiana benthamiana Kunitz peptidase inhibitor-like protein (KPILP) gene is induced in response to potato virus X (PVX) infection. Using reverse genetic approach, we have demonstrated that KPILP downregulates expression of LHCB1 and LHCB2 genes of antenna light-harvesting complex proteins, HEMA1 gene encoding glutamyl-tRNA reductase, which participates in tetrapyrrole biosynthesis, and RBCS1A gene encoding RuBisCO small subunit isoform involved in the antiviral immune response. Thus, KPILP is a regulator of chloroplast retrograde signaling system during developing PVX infection. Moreover, KPILP was demonstrated to affect carbon partitioning: reduced glucose levels during PVX infection were associated with KPILP upregulation. Another KPILP function is associated with plasmodesmata permeability control. Its ability to stimulate intercellular transport of reporter 2xGFP molecules indicates that KPILP is a positive plasmodesmata regulator. Moreover, natural KPILP glycosylation is indispensable for manifestation of this function. During PVX infection KPILP increased expression leads to the reduction of plasmodesmata callose deposition. These results could indicate that KPILP affects plasmodesmata permeability via callose-dependent mechanism. Thus, virus entering a cell and starting reproduction triggers KPILP expression, which leads to downregulation of nuclear-encoded chloroplast genes associated with retrograde signaling, reduction in photoassimilates accumulation and increase in intercellular transport, creating favorable conditions for reproduction and spread of viral infection.